A practical guide to sample size calculations: Installation of the app SampSize. (10th May 2022) - Flight, Laura; Julious, Steven A.
Abstract: In 2016 we published three articles in Pharmaceutical Statistics that gave a practical guide to sample size calculations. In each of the articles there were instructions on how to obtain the App SampSize. This short communication updates these instructions and highlights the updates and added functionality to the App.